Human capital and education policy: Evidence from survey data - Elisabeth Grewenig (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2021)
Elisabeth Grewenig prepared this study while she was working at the Center for Economics of Education at the ifo Institute. The study was completed in March 2021 and accepted as doctoral thesis by the Department of Economics at the LMU Munich. It consists of five distinct empirical essays that address various aspects of human capital formation and education policy. Chapters 2 and 3 are concerned with the determinants of human capital formation. In particular, chapter 2 investigates the impact of gender norms on labor-supply expectations of adolescents. Chapter 3 analyzes the effects of the Corona-induced school closures on students' time spent with different educational activities. Chapters 4 and 5 are concerned with the implementation and feasibility of educational reforms. Thereby, chapter 4 evaluates the impact of recent reforms on binding teacher recommendations by studying educational outcomes of students in primary and secondary schools. Chapter 5 examines whether support for educational policies is amenable to information provision about party-positions. Finally, chapter 6 contributes to the methodological debate around survey measurement by investigating belief elicitation in large-scale online surveys.
Keywords: C83; C90; C93; D30; D72; D83; H52; I21; I24; J13; J16; J22; J24; J62; P16; 330; Stranded assets; climate policy; expectations; utilities; event study; green innovation; patents; panel analysis; green finance; climate risk; intangible assets; institutional investors; renewable energy; crowding-out; regional economics; input-output ana; Gender Norms; Female Labor Supply; Survey Experiments; EducationalInequality; COVID-19; Low-Achieving Students; Home Schooling; DistanceTeaching; School Tracking; Admission Policies; Student Performance; Political Parties; Partisanship; Information; Endogenous Preferences; Voters; Family Policy; Beliefs; Incentives; Online Search